The effect of brain tomography findings on mortality in sniper shot head injuries. Issue 3 (30th November 2016) - Can, Çağdaş; Bolatkale, M; Sarıhan, A; Savran, Y; Acara, A Ç; Bulut, M
Abstract : Objectives: Penetrating gunshot head injuries have a poor prognosis and require prompt care. Brain CT is a routine component of the standard evaluation of head wounds and suspected brain injury. We aimed to investigate the effect of brain CT findings on mortality in gunshot head injury patients who were admitted to our emergency department (ED) from the Syrian Civil War. Methods: The study group comprised patients who were admitted to the ED with gunshot brain injury. Patients' GCS scores, prehospital intubations and brain CT findings were examined. Results: 104 patients were included (92% male, mean age 25 years). Pneumocephalus, midline shift, penetrating head injury, patients with GCS scores ≤6 and patients who had to be intubated in the prehospital period were associated with higher mortality (p<0.05). Discussion: The results of this study demonstrated that pneumocephalus, midline shift, a penetrating head injury, GCS scores ≤6 and prehospital intubation are associated with high mortality, whereas patients with temporal bone fracture, perforating or single cerebral lobe head injury had a higher survival rates. The temporal bone has a relatively thin and smooth shape compared with the other skull bones so a bullet is less fragmented when it has penetrated the temporal bone, which could be a reason for the reduced cavitation effect. In perforating head injury, the bullet makes a second hole and so will have deposited less energy than a retained bullet with a consequent reduction in intracranial injury and mortality. Further studies are required to reach definitive conclusions.